Rapid and simultaneous detection of Salmonella spp., Escherichia coli O157, and Listeria monocytogenes by magnetic capture hybridization and multiplex real-time PCR - Carloni, Elisa; Rotundo, Luca; Brandi, Giorgio; Amagliani, Giulia (Folia microbiologica, 2018)
The application of rapid, specific, and sensitive methods for pathogen detection and quantification is very advantageous in diagnosis of human pathogens in several applications, including food analysis. The aim of this study was the evaluation of a method for the multiplexed detection and quantification of three significant foodborne pathogenic species (Escherichia coli O157, Salmonella spp., and Listeria monocytogenes). The assay combines specific DNA extraction by multiplex magnetic capture hybridization (mMCH) with multiplex real-time PCR. The amplification assay showed linearity in the range 106-10 genomic units (GU)/PCR for each co-amplified species. The sensitivity corresponded to 1 GU/PCR for E. coli O157 and L. monocytogenes, and 10 GU/PCR for Salmonella spp. The immobilization process and the hybrid capture of the MCH showed good efficiency and reproducibility for all targets, allowing the combination in equal amounts of the different nanoparticle types in mMCH. MCH and mMCH efficiencies were similar. The detection limit of the method was 10 CFU in samples with individual pathogens and 102 CFU in samples with combination of the three pathogens in unequal amounts (amount's differences of 2 or 3 log). In conclusion, this multiplex molecular platform can be applied to determine the presence of target species in food samples after culture enrichment. In this way, this method could be a time-saving and sensitive tool to be used in routine diagnosis.
Keywords: Nucleic Acid Hybridization; multiplexová polymerázová řetězová reakce; lidé; Listeria monocytogenes; hybridizace nukleových kyselin; Multiplex Polymerase Chain Reaction; Escherichia coli O157; Salmonella; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans